The Impact of Family Poverty on Low Access to Technology in Education: Evidence in Surabaya - Yudha, Ana Toni Roby Candra; Septiani, Arinda; Arista, Setia Rini (Universitas Airlangga, 2024)
The current era of globalization has shown that technology is increasingly sophisticated, and development is becoming easier to optimize so that it is easier to distribute resources to remote and rural areas, but in reality, currently, the resources that have been entered are still experiencing inequality. One of them is the city of Surabaya. The number of poor people in the city of Surabaya has increased to 15 thousand people in 2020. As of 2021, the number of people in poverty increased to 152,490 thousand people. Final education is the most important capital to get a job and fulfill daily needs. This research uses a quantitative approach with a simple random sampling technique which is then analyzed using descriptive discussions. Data collection techniques were obtained from distributing questionnaires, interviews, and direct observation of 85 respondents/samples from a population of 575. Data testing was carried out using validity, reliability, classical assumption tests, and multiple linear regression analysis using SPSS 26. The results show that partial variables education (0.018), and access to technology (0.000) have a significant influence, while the number of families (0.369) does not have a significant influence on poor households. This research impacts government policy, especially in family poverty alleviation. Further studies could observe more about technology access in education on poverty alleviation.